High performance visible–near-infrared PbS-quantum-dots/indium Schottky diodes for photodetectors. (23rd December 2016) - Mi, Longfei; Wang, Hui; Zhang, Yan; Yao, Xudong; Chang, Yajing; Li, Guopeng; Li, Guohua; Jiang, Yang
Abstract: Here we fabricate self-powered photodetectors based on PbS-quantum-dots/indium Schottky barrier diodes successfully. These devices exhibit excellent repeatability and stability at a high frequency (up to1 MHz), and show a typical fast rise time/fall time of ∼0.8 μ s/3.2 μ s. They also show excellent rectification ratios up to 10 4 with bias from −0.5 V to +0.5 V in the dark and a pronounced photovoltaic performance under light illumination. Moreover, the devices demonstrate high sensitivity in weak light illumination detection (detectivity) approaching 10 12 Jones and low noise currents <1 pAHz −1/2 . These findings suggest great application potential of PbS-quantum-dots for advanced fast response, low noise current, high detectivity and high stability photodetectors.